2008
DOI: 10.1002/ptr.2514
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant, antinociceptive, and anti‐inflammatory activities of ethanol extracts from Aloe saponaria Haw.

Abstract: Aloe species are traditionally prescribed for hypertension, burning, and rheumatoid arthritis. To elucidate the mechanism of the antihypertensive and anti-inflammatory activities of this herb, the ethanol fraction from A. saponaria Haw. was evaluated for antioxidative activity using xanthine-xanthine oxidase (XO) assay, 2,2-Diphenyl-lpicrylhydrazyl radical (DPPH) assay, lipopolysaccharide (LPS)-induced nitric oxide (NO) production in RAW 264.7 cell, and antinociceptive activity using a tail-flick assay and hin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 32 publications
0
28
0
2
Order By: Relevance
“…The chemistry of the aloe plant has been studied for many years from a number of viewpoints [3,4,5,6,7,8,9,10,11,12]. Interest has centered on the parenchyma gel and its well-known therapeutic properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemistry of the aloe plant has been studied for many years from a number of viewpoints [3,4,5,6,7,8,9,10,11,12]. Interest has centered on the parenchyma gel and its well-known therapeutic properties.…”
Section: Resultsmentioning
confidence: 99%
“…Among the purported benefits of Aloe vera not supported by experimental or clinical data are the following: treatment of acne, haemorrhoids, psoriasis, anemia, glaucoma, petit ulcer, tuberculosis, blindness, seborrhoeic dermatitis, and fungal infections [2]. Several reports have demonstrated the antioxidant, antinociceptive and anti-inflammatory activities of the aloe species [3,4]. In addition, recent studies have shown the anti-cancer effect of aloe-emodin, an anthraquinone compound present in the leaves of Aloe vera [5].…”
Section: Introductionmentioning
confidence: 99%
“…Aloe vera is used both internally and externally on humans in a form of alternative medicine as well as in the home in first aid. It has been shown that Aloe vera expresses wound-and burn-healing effects and shows immunomodulatory, anti-inflammatory, antiparasitic, UV protective, antioxidant, antiviral, antitumor and antidiabetic activities (Lee et al, 2000;Choi & Chung, 2003;Sarkar et al, 2005;Yoo et al, 2008;Kigondu et al, 2009;Ozsoy et al, 2009). Telefo et al (1998Telefo et al ( , 2002Telefo et al ( , 2004) also demonstrated the effect of Aloe vera on the reproductive system in rats where the plant extract regulated the steroidogenesis and hormone levels, menstrual cycle, ovarian and uterine weight and was used to treat dysmenorrhea or infertility.…”
Section: Introductionmentioning
confidence: 99%
“…Telefo et al (1998Telefo et al ( , 2002Telefo et al ( , 2004) also demonstrated the effect of Aloe vera on the reproductive system in rats where the plant extract regulated the steroidogenesis and hormone levels, menstrual cycle, ovarian and uterine weight and was used to treat dysmenorrhea or infertility. These medicinal properties are mainly mediated through biologically active components in Aloe vera and its extracts such as anthraquinones, flavonoids, phenolic acids, antioxidant vitamins, enzymes and other non-nutrient compounds of the plant (Choi & Chung, 2003;Hu et al, 2003;Yoo et al, 2008). Pharmacological action of Aloe vera extracts is closely related to cytokine network maintenance or radical level stabilization among others in eye tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been used as an agent in treatment of peptic ulcers, diabetes mellitus, and cancer 8,10 . The ethanol extract of A. saponaria has pharmacological properties, including anti-oxidant, antinociceptive, and anti-inflammatory activity 11 . Research on medicinal active compounds of Aloe has developed in scope during the last three decades and the production or transformation of valueadded compounds, which are medicinally important, still needs to be investigated.…”
mentioning
confidence: 99%